2002
DOI: 10.1007/s00253-002-1091-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of chromate: thermodynamic analysis of the effects of Cr(VI) on sulfate-reducing bacteria

Abstract: Developing new bioremediation processes for soils and effluents polluted by Cr(VI) requires the selection of the most efficient and the most heavy-metal-resistant bacteria. The effects of Cr(VI) on bioenergetic metabolism in two sulfate-reducing bacteria (SRB), Desulfovibrio vulgaris Hildenborough and Desulfomicrobium norvegicum, were monitored using isothermal microcalorimetry. The complete reduction of Cr(VI) to Cr(III) was studied by spectrophotometry and by speciation using a combination of high-performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Despite the undesirable features of this metabolic end product, SRB have been exploited in studies of heavy metal bioremediation (Jiang and Fan, 2008; Martins et al, 2009) because of the ability of sulfide to form insoluble complexes with heavy metals (Jalali and Baldwin, 2000). SRB also precipitate heavy metals by directly changing the metal redox state to a less soluble form (Lovley et al, 1993a,b; Lloyd et al, 1999; Chardin et al, 2003). The metabolism of SRB is studied, therefore, to understand how to minimize the detrimental economic effects of these bacteria and to maximize their positive metabolic traits.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the undesirable features of this metabolic end product, SRB have been exploited in studies of heavy metal bioremediation (Jiang and Fan, 2008; Martins et al, 2009) because of the ability of sulfide to form insoluble complexes with heavy metals (Jalali and Baldwin, 2000). SRB also precipitate heavy metals by directly changing the metal redox state to a less soluble form (Lovley et al, 1993a,b; Lloyd et al, 1999; Chardin et al, 2003). The metabolism of SRB is studied, therefore, to understand how to minimize the detrimental economic effects of these bacteria and to maximize their positive metabolic traits.…”
Section: Introductionmentioning
confidence: 99%
“…However, at higher aeration level the Cr(VI) reduction started to decline. Chromate reduction has been reported by both aerobic (Desai et al 2008a;Poopal and Laxman, 2009) and anaerobic bacteria (Michel et al 2001;Chardin et al 2002). In the presence of oxygen, bacterial Cr 6+ reduction commonly occurs as a two-or three-step process with Cr 6+ initially reduced to the shortlived intermediates Cr 5+ and/or Cr 4+ before further reduction to the thermodynamically stable end product, Cr 3+ (Cheung and Gu, 2007).Cr 3+ (Cheung and Gu, 2007).…”
Section: Fig 5 Effect Of Aeration Level (Shaking Rpm) On the Growth mentioning
confidence: 99%
“…In fact, it is common practice to stimulate growth of existing microorganisms by injecting an excess electron donor into the subsurface, creating an electron acceptor limited environment. Previous studies have reported that substrate limitation can increase Cr(VI) susceptibility (Chardin et al 2002 ), and injections of electron donor without a corresponding increase in electron acceptor creates unbalanced electron donor to acceptor ratios. However, little is known about the physiological responses of metal-reducing populations in the context of unbalanced ratios that occur as a consequence of stimulated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Desulfovibrio species are model sulfate-reducing bacteria (SRB) and have been shown to reduce metals, metalloids, and radionuclides (Heidelberg et al 2004 ; Klonowska et al 2008 ; Zhou et al 2014 ). Previous work with purified enzymes and whole cells has shown that Desulfovibrio vulgaris is capable of reducing Cr(VI) via hydrogenases and cytochrome c3, but cells are unable to use Cr(VI) as a terminal electron acceptor linked to growth (Lovley and Phillips 1994 ; Chardin et al 2002 ; Elias et al 2004 ). One promising approach for treatment of contaminated environments is in situ biostimulation, the process of promoting indigenous microbial activity via the addition of carbon, nitrogen, phosphorus, and/or energy sources (Tyagi et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%